The Efectiveness of Aerobic Gymnastics on Blood Pressure Control in Hypertensive Clients in Banyuwangi - Haswita, Haswita; Wijaya, Novita; Amin, Yusron; Makrup, Makrup (Fakultas Kedokteran, 2025)
Hypertension is a common circulatory disorder in the community that, if not promptly managed, can lead to death and various complications. Therefore, effective blood pressure management is crucial, and one effective method is aerobic exercise. This research aims to analyze the effectiveness of aerobic exercise on blood pressure control in hypertension clients in Desa Genteng Kulon, Banyuwangi. This research is a quantitative study with a pre-experimental design, specifically a one-group pre-posttest design. The sample consisted of 38 participants, selected using purposive sampling. The research instruments included observation sheets, Standard Operating Procedures (SOP), sphygmomanometers, and stethoscopes. Data were analyzed using the Wilcoxon signed-rank test to determine the impact of aerobic exercise on blood pressure before and after the intervention. The results showed that the pre study, blood pressure of the majority of respondents, 18 respondents (47.4%) were in the grade 1 hypertension category and 12 respondents (31.6%) were in grade 2 hypertension. Meanwhile, post study, blood pressure showed that 15 respondents (39.5%) were in the grade 1 hypertension, 14 respondents (36.8%) were pre-hypertensive and 8 people (21.1%) were normal. The Wilcoxon t-test showed a p-value of 0.000<0.05, so there was a significant effect on blood pressure between before and after giving aerobic exercise. This study is expected to provide valuable information and suggest that hypertension patients incorporate regular aerobic exercise into their routines, as it can enhance daily physical activity and serve as an alternative for prevention and treatment of hypertension.